PERAN COST CONTROL DAN VARIANCE ANALYSIS TERHADAP KINERJA SEKRETARIAT DPRD KABUPATEN GOWA - Syamsuriani; Mira; Masrullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of Cost Control and Variance Analysis on the Performance of the Secretariat of the Regional House of Representatives (DPRD) of Gowa Regency. This research employed a quantitative approach using explanatory research design. Primary data were collected through questionnaires distributed to employees of the DPRD Secretariat of Gowa Regency. The research sample consisted of 31 respondents selected using the saturated sampling technique. Data analysis methods included descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS for Windows 24.0. The results indicate that the Cost Control variable does not have a significant effect on organizational performance, with a regression coefficient of -0.164 and a significance value of 0.348 (> 0.05). This finding suggests that the implementation of cost control has not been able to provide a meaningful impact on improving organizational performance, as budget management is still more oriented toward administrative compliance than toward performance effectiveness. Meanwhile, the Variance Analysis variable has a positive and significant effect on performance, with a regression coefficient of 0.498 and a significance value of 0.016 (< 0.05). This finding indicates that the better the variance analysis process, the better the organizational performance. The coefficient of determination (Adjusted R²) of 0.140 indicates that 14% of the variation in performance can be explained by the two independent variables. This study implies that public sector organizations need to optimize variance analysis as a strategic decision-making tool in budget evaluation to improve organizational performance effectiveness.